La Discalculia en la enseñanza de la Matemática - Ortega Gamboa, Mabelin Cristina (2024)
The purpose of this work is to analyze dyscalculia in the mathematics teaching, this allows the teacher to have knowledge about the subject and in the same way treat dyscalculia through the use of new strategies, achieving the development of skills and abilities in each one of the students; also overcome the difficulties they present in the mathematics area. The research project was developed at the Félix Valencia Educational Unit with the following problem: how does dyscalculia affect the teaching of mathematics to children in the seventh year of BGE at the Félix Valencia Educational Unit, Cotopaxi province, Latacunga canton, Joseguango Bajo parish, in the 2023-2024 school year? Therefore, to find a solution to this problem, the general objective was formulated: Establish the incidence of dyscalculia in mathematics teaching. The mixed approach is applied in the research, and the types of bibliographic and documentary research were used; In addition, the methods used were deductive and inductive, techniques such as interviews and surveys were used too. With the information obtained, the following conclusion was reached: the lack of understanding of dyscalculia by teachers represents a significant obstacle to students learning, negatively affecting their school performance. This research contributes to the implementation of pedagogical strategies adapted to provide effective support to students who face the disorder of dyscalculia.